An Examination of the Holism Paradigm: A View of Social Work. Issue 8 (17th November 2017) - Ashcroft, Rachelle; Van Katwyk, Trish; Hogarth, Kathy
ABSTRACT: This article examines the holism paradigm, implications on social work practice in healthcare, and how social work practice can help promote the value of social justice. Examining the holistic health paradigm fosters a critical reflection that assists to better understand beliefs and assumptions that guide social work practice, thus leading to critical action.